Reproducibility of quantitative susceptibility mapping in the brain at two field strengths from two vendors. Issue 6 (9th May 2015) - Deh, Kofi; Nguyen, Thanh D.; Eskreis‐Winkler, Sarah; Prince, Martin R.; Spincemaille, Pascal; Gauthier, Susan; Kovanlikaya, Ilhami; Zhang, Yan; Wang, Yi
Abstract : Purpose: To assess the reproducibility of brain quantitative susceptibility mapping (QSM) in healthy subjects and in patients with multiple sclerosis (MS) on 1.5 and 3T scanners from two vendors. Materials and Methods: Ten healthy volunteers and 10 patients were scanned twice on a 3T scanner from one vendor. The healthy volunteers were also scanned on a 1.5T scanner from the same vendor and on a 3T scanner from a second vendor. Similar imaging parameters were used for all scans. QSM images were reconstructed using a recently developed nonlinear morphology‐enabled dipole inversion (MEDI) algorithm with L1 regularization. Region‐of‐interest (ROI) measurements were obtained for 20 major brain structures. Reproducibility was evaluated with voxel‐wise and ROI‐based Bland–Altman plots and linear correlation analysis. Results: ROI‐based QSM measurements showed excellent correlation between all repeated scans (correlation coefficient R ≥ 0.97), with a mean difference of less than 1.24 ppb (healthy subjects) and 4.15 ppb (patients), and 95% limits of agreements of within −25.5 to 25.0 ppb (healthy subjects) and −35.8 to 27.6 ppb (patients). Voxel‐based QSM measurements had a good correlation (0.64 ≤ R ≤ 0.88) and limits of agreements of −60 to 60 ppb or less. Conclusion: Brain QSM measurements have good interscanner and same‐scanner reproducibility for healthy and MS subjects, respectively, on the systems evaluated in this study. J. MAGN. RESON. IMAGING 2015;42:1592–1600.